Analisis Pengaruh Literasi Keuangan, Perilaku Keuangan, dan Pendapatan Terhadap Minat Keputusan Berinvestasi - Farhanyudha, Giffari Muhammad; Atmini, Sari (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2024)
This research aims to analyze the effect of financial literacy, responsible financial behavior, and income on the intention of investment decisions by applying the theory of planned behavior and the theory of behavioral finance. The samples in this research involve university students in Malang, including 100 respondents selected through the purposive sampling method. The data from respondents are collected through a survey utilizing questionnaires, and analyzed by multiple regression. The results exhibited that financial literacy and income had a positive effect on the intention of investment decisions, which corresponds to the hypotheses. However, responsible financial behavior did not affect the intention of investment decisions.